Characterization of the bacterial community composition in water of drinking water production and distribution systems in Flanders, Belgium. Issue 5 (14th October 2018) - Van Assche, Ado; Crauwels, Sam; De Brabanter, Joseph; Willems, Kris A.; Lievens, Bart
Abstract: The quality of drinking water is influenced by its chemical and microbial composition which in turn may be affected by the source water and the different processes applied in drinking water purification systems. In this study, we investigated the bacterial diversity in different water samples from the production and distribution chain of thirteen drinking water production and distribution systems from Flanders (Belgium) that use surface water or groundwater as source water. Water samples were collected over two seasons from the source water, the processed drinking water within the production facility and out of the tap in houses along its distribution network. 454‐pyrosequencing of 16S ribosomal RNA gene sequences revealed a total of 1, 570 species‐level bacterial operational taxonomic units. Strong differences in community composition were found between processed drinking water samples originating from companies that use surface water and other that use groundwater as source water. Proteobacteria was the most abundant phylum in all samples. Yet, several phyla including Actinobacteria were significantly more abundant in surface water while Cyanobacteria were more abundant in surface water and processed water originating from surface water. Gallionella, Acinetobacter, and Pseudomonas were the three most abundant genera detected. Members of the Acinetobacter genus were even found at a relative read abundance of up to 47.5% in processed water samples, indicating a general occurrence of Acinetobacter in drinking water (systems). Abstract : Bacterial community compositions of 13 drinking water production and distribution systems in Flanders (Belgium) were characterized using 454‐pyrosequencing. Clear differences in community composition were found in drinking water originating from groundwater or surface water. Several communities were dominated by the Acinetobacter genus.